Dante’s Choreographies of Celebration - Webb, Heather (Quaderni d'Italianistica)

(untitled) (Iter Press, 2024)
Numerous episodes in the Commedia present themselves as “scenes,” as interactions between characters that have a highly dramatic quality. These “scenes” would resonate, for medieval audiences, with their personal experiences of live performance events as well as depictions of related scenes in the visual arts that were visible in local churches and baptisteries. This essay takes Dante’s staging of the encounter with Sordello in Purgatorio 6 as a central case study of a scene of celebration with multiple resonances, exploring the ways in which that episode might bring to a reader’s mind visual and textual performances of the Visitation. By contextualizing the scene within relevant medieval modes of performing and viewing affectively powerful scenes, the essay proposes that known scenes of the Visitation might be implicitly employed in Dante’s text to enrich the affective charge of the depiction of the meeting with Sordello.